A short overview of Power-to-Methane: Coupling preparation of feed gas with CO2 methanation. (15th June 2023) - Liu, Zhihao; Gao, Xinhua; Wang, Kangzhou; Liang, Jie; Jiang, Yongjun; Ma, Qingxiang; Zhao, Tian-Sheng; Zhang, Jianli
Graphical abstract: Abstract: Power to Methane (PtM) technology is a multi-stage process where H2 is first produced by water splitting, which subsequently reacts with CO2 to produce methane. This strategy not only enables CO2 resource utilization, but offers a promising pathway for the production of fuels. To date, PtM technology chain still lacks in a detailed summary and discussion and the potential for low-temperature methanation is less understood. Therefore, it is significative to review the state of the art of whole PtM process. In this review, firstly, the representative water electrolysis and CO2 separation and capture technologies are addressed briefly. Second, the development status of efficient CO2 methanation catalysts at low temperature (≤300 °C) is evaluated. Finally, the challenges and application prospects of PtM technology are discussed. This work might lead to a better understanding to PtM technology and provide a reference for the rational design of low-temperature methanation catalysts in industry.